Outsourcing and the demand for low-skill labour in German manufacturing : new evidence - Ingo Geishecker (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper analyses how international outsourcing has affected the relative demand for low skilled workers in Germany during the 1990s. In contrast to previous empirical work, the single elements of the input-output-matrix are used to disentangle international outsourcing and trade in final goods more accurately. The main finding is that during the 1990s international outsourcing had a significant negative impact on the relative demand for low-skilled workers, explaining between 19% and 24% of the overall decline in the relative demand for low-skilled labour
Keywords: F20; J23; J31; 330; international trade; outsourcing; skill-bias; labour demand; Outsourcing; Internationale Arbeitsteilung; Verarbeitendes Gewerbe; Arbeitsnachfrage; Ungelernte Arbeitskräfte; Schätzung; Deutschland